PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN LEARNING STYLE DALAM KEGIATAN REMIDI - Widayanti, Febi Dwi (Jurnal Likhitaprajna, 2018)
This study aims to (1) find out the differences in student learning outcomes through cooperative learning Jigsaw model with conventional learning on the subject of the Chemistry Association, (2) know the implementation of chemical learning using the Jigsaw model on the subject of the Chemical Association, (3) know the application of remedial programs with pay attention to the learning style of students in the Chemical Bond material to the completeness of student learning. In this study using a real and descriptive experimental research design. The design of this study aims to reveal a causal relationship by involving a control group in addition to the experimental group. The design chosen in this study was a post-test design with randomized group selection. The results of this study indicate that students 'chemistry learning outcomes through jigsaw learning and remedial activities by paying attention to learning styles are higher than students' chemistry learning outcomes through conventional learning and remedial activities without regard to student learning styles.Keywords: learning style, cooperative, jigsaw, remidial